Mechanical reinforcement of complex shaped ceramic filter fabricated using binder jetting process with photocurable composite ink - Jong-Han Choi; Mose Kwon; Kwang-Taek Hwang; Jin-Ho Kim; Jung-Hoon Choi; Ung-Soo Kim; Kyu-Sung Han (Journal of Materials Research and Technology)
Porous ceramics are widely used in various industries of separation, storage, and insulation. However, conventional manufacturing processes such as pressing and casting have difficulty in producing complex shaped ceramic objects. Binder jetting which is powder based additive manufacturing technology offers advantages in producing porous ceramic components. However, green bodies manufactured using binder jetting often lack strength, resulting in breakage during post processing such as de-powdering and sintering. This study explored binder jetting process that strengthens green and sintered bodies of porous ceramic filters with complex structures. The powder flowability was enhanced by flow agent addition and the conventional water-based binder was replaced with the photocurable composite binder ink. As a result, the fabricated filter demonstrated porosity of 60.78% and mechanical strength of 8.34 MPa. This approach enabled the successful manufacturing of complex shaped alumina filters with sufficient porosity and strength to withstand post-processing.